2009
DOI: 10.1007/s00500-009-0402-8
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the propositional logic of a t-norm with truth-constants: completeness results for rational semantics

Abstract: In this paper we consider the expansions of logics of a left-continuous t-norm with truth-constants from a subalgebra of the rational unit interval. From known results on standard semantics, we study completeness for these propositional logics with respect to chains defined over the rational unit interval with a special attention to the completeness with respect to the canonical chain, i.e. the algebra over ½0; 1 \ Q where each truth-constant is interpreted in its corresponding rational truth-value. Finally, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…We denote by RC ev , FSRC ev , SRC ev , QC ev , FSQC ev , SQC ev the restriction of the properties we have been studying in the previous section to evaluated formulae (in the case of continuous t-norm based logics), or to positively evaluated formulae (in the case of WNM-t-norm based logics). 19 These completeness properties are straightforwardly refuted in many cases. Namely, for each * ∈ CONT-fin \ { * G } L * ∀ has not the RC and thus there is a constant-free formula ϕ such that L * ∀ ϕ and |= [0,1] * ϕ, and hence, since ϕ is equivalent to the evaluated formula 1 → ϕ and L * ∀(C) is a conservative expansion of L * ∀, we also have a counterexample to the RC ev of L * ∀(C).…”
Section: The Case Of Evaluated Formulaementioning
confidence: 94%
See 4 more Smart Citations
“…We denote by RC ev , FSRC ev , SRC ev , QC ev , FSQC ev , SQC ev the restriction of the properties we have been studying in the previous section to evaluated formulae (in the case of continuous t-norm based logics), or to positively evaluated formulae (in the case of WNM-t-norm based logics). 19 These completeness properties are straightforwardly refuted in many cases. Namely, for each * ∈ CONT-fin \ { * G } L * ∀ has not the RC and thus there is a constant-free formula ϕ such that L * ∀ ϕ and |= [0,1] * ϕ, and hence, since ϕ is equivalent to the evaluated formula 1 → ϕ and L * ∀(C) is a conservative expansion of L * ∀, we also have a counterexample to the RC ev of L * ∀(C).…”
Section: The Case Of Evaluated Formulaementioning
confidence: 94%
“…As it regards to canonical strong completeness for evaluated formulae, both for the real and rational semantics, in [19] it is shown that it almost always fails. Indeed, it is only true for expansions of G, NM, L ⊗ and L when the algebra C of truthconstants satisfies the following topological property: it has no positive sup-accessible points, i.e.…”
Section: Yes Nomentioning
confidence: 97%
See 3 more Smart Citations